Are Malaysian TVET graduates ready for the future?. (4th March 2021) - Kenayathulla, Husaina Banu
Abstract: Currently, we are at the beginning of the Fourth Industrial Revolution, where the rapid developments in genetics, artificial intelligence, robotics, nanotechnology, 3D printing and biotechnology are growing rapidly. It is expected that the majority of the children entering primary school today might end up working in jobs that do not yet exist. In such a fast‐changing employment landscape, the ability to prepare for future skills will be required to take advantage of the opportunities presented by these trends. National Dual Training System has been implemented by the Ministry of Human Resource to ensure TVET graduates are equipped with the employability skills needed in the job market. Questionnaires were distributed to employers from different training institutions, industries and agencies. The employers were to evaluate the level of employability skills obtained by the graduates that had gone through the National Dual Training System and then, the employers were asked to identify employability skills needed to meet employment demands in the Fourth Industry Revolution. The findings provide insights to the policymakers and curriculum developers on the appropriate interventions that need to be taken to ensure our graduates are well equipped with the employability skills needed for the future. ABSTRAK: Kini, kita berada di awal Revolusi Industri Keempat, di mana perkembangan pesat dalam genetik, kecerdasan buatan, robotik, nanoteknologi, percetakan 3D dan bioteknologi berkembang secara pesat. Dijangkakan majoriti kanak‐kanak yang memasuki sekolah rendah hari ini mungkin akhirnya bekerja dalam pekerjaan yang masih belum wujud. Dalam lanskap pekerjaan yang cepat berubah, kemampuan untuk mempersiapkan kemahiran masa depan diperlukan untuk memanfaatkan peluang yang ditunjukkan oleh trend ini. Sistem Latihan Dual Nasional telah dilaksanakan oleh Kementerian Sumber Manusia untuk memastikan graduan TVET dilengkapi dengan kemahiran kerja yang diperlukan dalam pasaran pekerjaan. Soal selidik diedarkan kepada majikan dari pelbagai institusi latihan, industri dan agensi. Majikan menilai tahap kemahiran kebolehkerjaan siswazah yang telah melalui Sistem Latihan Dual Nasional dan seterusnya, para majikan diminta untuk mengenalpasti kemahiran kebolehkerjaan yang diperlukan untuk memenuhi tuntutan pekerjaan dalam Revolusi Industri Keempat. Dapatan kajian ini dapat memberi pandangan kepada penggubal dasar dan pembangun kurikulum mengenai campur tangan sesuai yang perlu dilakukan untuk memastikan graduan dilengkapi dengan kemahiran kerja yang diperlukan untuk masa depan.